Compact Liquid Crystal Polymer-Based Tri-Band Flexible Antenna for WLAN/WiMAX/5G Applications - Chengzhu Du; Xiaodi Li; Shunshi Zhong (IEEE Access)
In this paper, a new compact coplanar waveguide (CPW)-fed liquid crystal polymer (LCP) based tri-band antenna is presented and fabricated for Wireless Local Area Network (WLAN), Worldwide Interoperability for Microwave Access (WiMAX) and 5th-Generation (5G) systems. The antenna combines two strips with the main radiation rectangular patch and coplanar waveguide ground. The proposed antenna is printed on a LCP substrate with a thickness of 0.1 mm and has a small overall dimensions of 20mm $× 32$ mm $× 0.1$ mm. To analyze the characteristics, the antenna is designed and fabricated, and then the performance of the antenna is measured and tested. The measurement results show that the proposed antenna has three operating bandwidths, including 2.38 – 2.79 GHz, 3.27 – 4.05 GHz, and 4.80 – 8.44 GHz. To test the flexibility of the antenna, the antenna is simulated and measured in bent configurations for radii of 10 mm and 50 mm. In addition, the antenna is attached to different parts of the human body to test the integration effect in wearable equipment. The experimental results show that the performance of the antenna remains reliable under bending conditions and that the specific absorption ratio (SAR) value meets the European Union (EU) standard. The proposed antenna shows reasonable gains and good radiation characteristics in the operating bands. The flexible, compact, simple design and multiband performance indicates that the antenna is suitable for integration in flexible electronic devices.